Pengaruh Edukasi Gizi Terhadap Pengetahuan Pencegahan Anemia Remaja Di Madrasah Tsanawiyah Negeri 02 Kota Bengkulu - Syafitri, Irfina; Husin, Hasan; Afriyanto; Angraini, Wulan (Politeknik Kesehatan Kemenkes Bengkulu, 2024)
Problem: Adolescent girls are very susceptible to anemia, especially those who have menstruated. Anemia in adolescents is caused by nutritional deficiencies, especially iron and folic acid. Due to poor knowledge of diet or incorrect understanding of the body's need for macro- and micronutrients, this intake is low. Anemia in adolescent girls is still a major health problem because its prevalence is still above 20%, namely 21.7%. The Aim Of The Research: This study aims to determine the effect of nutrition education on knowledge of anemia prevention among female adolescents at MTsN 02 Bengkulu City. Research Method: For this research, a quasi-experimental research design with a pre-test-post-test control group design was used. The population is all young women at MTsN 02 Bengkulu City with a sample of 112 respondents. The data collection technique uses a questionnaire, before being given education, respondents are given a pretest, then the education is given using the lecture method with leaflets and the animated video method, carried out in 3 meetings with a distance of 1 day and after the 3rd meeting they are immediately given a post test with the same questionnaire. Results: there is an effect of providing nutrition education using the animated video method on increasing knowledge of young women about anemia at MTsN 02 Bengkulu City, shown by a p-value of 0.018, which means a p-value <0.05. Conclusion: The animated video method has a significant impact in increasing awareness of young women about how to prevent anemia.